O papel do Banco Mundial no rural brasileiro: analisando a estratégia alianças produtivas - Tiba, Thiago (Universidade Federal de São Carlos, 2025)
This study examines the role of the World Bank in rural Brazil through the Productive Alliances (AP) strategy, designed to foster the market integration of family farmers into higher value-added supply chains. The analysis is grounded in the premise that international organizations exert substantial influence on the formulation and implementation of public policies targeting rural populations. Within this context, AP has emerged as one of the principal instruments for advancing rural development in the country. The study aimed to evaluate the implementation of AP-related projects in Brazil by identifying their foundational principles, financial allocations, achieved outcomes, and beneficiary profiles. Methodologically, the research employed a documentary approach based on official World Bank reports, enabling a detailed examination of each project's components, investment structure, and performance targets. The results indicate that AP initiatives expanded market access, strengthened producer organizations, and supported improvements in water-related infrastructure. Overall, the strategy has met its core objectives in Brazil, generating significant impacts on household income, agricultural competitiveness, and the economic inclusion of family farmers.
The role of the World Bank in rural brazil: an analysis of the productive alliances strategy
Keywords: Alianças produtivas; Banco Mundial; Extensão rural; Productive alliances; Rural extension; World Bank; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; 2. Fome Zero e Agricultura Sustentável